1994
DOI: 10.1111/j.1432-1033.1994.tb18726.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterisation of purified human wild‐type p53 overexpressed in insect cells

Abstract: Conditions for the overexpression of human wild-type p53 using a baculovirus construct were optimised in insect cells which produced up to 20 mg p53/1 culture. Milligram amounts of p53 were purified to apparent homogeneity using chromatography on double-stranded DNA-cellulose (=58 % yield) followed by immunoaffinity chromatography with an epitope elution step (up to 48% yields) at 4°C. The M, of extracted p53 both from insect cell lysates and after purification was 54000 by SDSPAGE. Isoelectric focusing showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…1A, a band corresponding to the molecular weight of non‐ubiquitinated p53 could be detected in this assay. This band appeared even in the absence of ectopic His 6 ‐tagged ubiquitin and therefore could be due to non‐specific binding of p53 to the nickel‐agarose beads or to the ability of p53 to bind to nickel as reported by others [16,17].…”
Section: Resultsmentioning
confidence: 52%
“…1A, a band corresponding to the molecular weight of non‐ubiquitinated p53 could be detected in this assay. This band appeared even in the absence of ectopic His 6 ‐tagged ubiquitin and therefore could be due to non‐specific binding of p53 to the nickel‐agarose beads or to the ability of p53 to bind to nickel as reported by others [16,17].…”
Section: Resultsmentioning
confidence: 52%
“…The average radii Ru of the unaggregated protein, evaluated from the τ1s, range from 8 to 12 nm(Figure 4b), substantially greater than the ca. 4 nm radius expected for a p53 tetramer of molecular weight 175 kg mol -1 58. Consonantly with the exaggerated radius, the considerable polydispersity µτ 2 ≈ 0.35 -0.25(Figure 4c) indicates the dominance of highorder oligomers over monomeric, dimeric, and tetrameric p53 units.14,59 To further explore how temperature manipulates the state of the unaggregated protein, we measured average protein molecular weight Mw using static light scattering at 15, 24, and 37 o C(Figure 4d,e).…”
mentioning
confidence: 94%
“…The dependence of complex formation on the presence of Zn 2ϩ was further established by titrating EDTA into the reaction. Since it has been shown that other divalent cations may bind to p53, the influence of other such ions (Ca 2ϩ , Cd 2ϩ , Co 2ϩ , Cu 2ϩ , Mg 2ϩ , Mn 2ϩ , and Ni 2ϩ ) on the formation of TAg-p53 complexes in this ELISA was investigated in the same manner as for Zn 2ϩ ; all ion solutions were prepared from the chloride salt (30).…”
Section: Methodsmentioning
confidence: 99%